Analisis Rasio Likuiditas Terhadap Kinerja Keuangan Pada PT. Semen Baturaja,Tbk - Triana Agustini; Widarti Widarti; Zulfadhli Zulfadhli; Saipul Anuar (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The purpose of this study was to determine the financial performance of PT. Semen Baturaja (Persero) Tbk based on liquidity ratio analysis. By using financial statements as the basis for assessing financial performance. The analytical method used is a liquidity ratio that uses several assessments, namely the current ratio, the quick ratio, and the cash ratio. The results showed that the liquidity ratio in the calculation of the current ratio, quick ratio, and cash ratio at PT. Semen Baturaja (Persero) Tbk experienced fluctuations or ups and downs. The Current Ratio decreased in 2017 and increased again in 2018 and 2019, the Quick Ratio decreased from 2016 to 2020, and the Cash Ratio increased in 2017-2018 and decreased in 2019-2020. The average liquidity ratio is below the established industry standard, which means that the company's ability to meet its obligations is still not good. This is because the company has not been able to constantly increase current assets and has not been able to increase the value of current liabilities.